CAUSE: A multidimensional framework for a digital inclusivity index for food, land, and water systems - Opola, Felix Ouko; Langan, Simon J.; Arulingam, Indika; Schumann, Charlotte; Singaraju, Niyati; Joshi, Deepa; Ghosh, Surajit (CGIAR, 2023)
As we embark on the 'fourth industrial revolution', digital innovation emerges as a promising solution to critical challenges in food production, consumption, and the supportive triad of food, land, and water systems. This potential is particularly pronounced in less industrialised, agrarian-based economies. Digital advancements promise enhanced communication, improved data management, democratic and transparent governance, accessible financial services, and decision-making support. Nevertheless, there are rising concerns about the risk of digital innovation bypassing individuals with scant education, scarce resources, native populations, and susceptible demographics such as women and young people, thus depriving them of its advantages. Additionally, the potential harms of digital technologies to these populations and society are worth considerable attention. This article addresses the concept of digital inclusivity within food, land, and water systems, emphasising the diverse needs of various groups, particularly those managing smallholder land holdings. We present evidence from peer-reviewed literature and other sources supporting the need for inclusive digital innovation. We introduce a comprehensive five-dimensional framework CAUSE (Consequences, Accessibility, Usefulness, Support, Enabling) with twenty-two indicators to foster digital inclusivity. Building on this framework, we propose a 'Digital Inclusivity Index' encompassing these multidimensional aspects. The paper argues for a broader 'digital ecosystem' perspective, where collaborative knowledge and resource sharing enhance digital innovation, extending beyond mere technology adoption to include shifts in existing social structures and institutions. Thus, the CAUSE framework helps in enabling wider access to digital innovation and has the useful consequence of increased support for its practical applications, enhancing its overall usefulness to society.